Cost Implications for the Construction of Earthquake Resistant Load Bearing Residential Building - Mishra, Anjay Kumar (Journal of Advanced Research in Geo Sciences & Remote Sensing, 2021)
This study was conducted to analyze the Cost Implication for the Construction of Earthquake Resistant Load Bearing Residential Building with a case of Ramechhap District of Nepal. Analysis has been done by using NRA for design, District rate 072/073 from DDC Ramechhap for cost estimate, NBC Code to show the features of earthquake resistant load bearing building. The cost of these models were ranging from Rs. 4,01,643.36 to 21,21,078.75 for constructing of residential building. Rs. 4,01,643.36 seems to be the lowest cost for SMC-1.2 model and Rs 21,21,078.75 is the highest cost for BMC-2.4 But According to Plinth Area rate, Minimum Cost was taken by SMM 1.1. and it had taken Rs. 8, 52,950.64. The cost difference between earthquake resistant building and convention type building was found to be Rs. 2,10,345.09 which is 16.67% cost more than conventional type building and also the cost of earthquake resistant features is the cost difference between the earthquake-resistant building and conventional type building. How to cite this article: Mishra AK. Cost Implications for the Construction of Earthquake Resistant Load Bearing Residential Building. J Adv Res Geo Sci Rem Sens 2019; 6(3&4): 3-15. DOI: https://doi.org/10.24321/2455.3190.201903